Financial constraints and the value of cash holdings - Zhang, Yuchi (2013)
Financial constraint is an important topic in corporate finance. Previous literatures do researches on how to do measurement on financial constraint and whether it has an impact on investment and cash holdings. The results of these articles indicate that financial constraints do have influence on cash holdings. This dissertation will analyze the association between cash holdings and the value of companies in financially constrained and unconstrained firms based on some existing conclusions. We need to check two problems. One is whether cash holdings more valuable in constrained companies, and the other one is why cash holdings more valuable in these companies.